REPRESENTASI KRITIK SOSIAL DALAM TEKS LAGU BENTO KARYA IWAN FALS : SEBUAH ANALISIS WACANA MENGENAI FUNGSI BAHASA (PRAGMATIK) - Kaleb E. Simanungkalit (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
Music is a tool for musicians to express what you want delivered. In the song "Bento" by Iwan Fals and Naniel is a very nice song and able to attract the attention of various circles. Song Iwan Fals is dominated by social criticism to the government during the New Order. Based on the analysis of the author with the study of pragmatic model Teun Van A. Djik find that song Bento is a social critique of the authorities / executives in the New Order. In this work also contains the criticism against officials who use their position to enrich themselves.